Diplomasi Transisi Energi Indonesia: Strategi Lingkungan dan Negosiasi Investasi Hijau Global Periode 2023–2025 - Akwal Waffi Kariswan; Maulana Fasha Aralea; Sekar Rahayu; Syifa Nindia Destiany; Diyah Pitaloka Rizki (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
The global energy transition has made green investment a strategic issue in international relations, particularly for developing countries facing funding constraints and dependence on fossil fuels. Indonesia is in a crucial position due to its significant renewable energy potential, yet its continued reliance on coal as its primary energy source. This article aims to analyze Indonesia's energy transition diplomacy in attracting and managing global green investment in the 2023–2025 period. This research employs a qualitative approach, employing literature review and foreign policy analysis. Data were obtained from official government documents, international organization reports, and relevant scientific publications, and then analyzed using an environmental diplomacy framework. The analysis focuses on Indonesia's strategy for energy transition cooperation, particularly through the Just Energy Transition Partnership (JETP) scheme and involvement in global climate forums. The results show that Indonesia adopts an adaptive diplomatic strategy by balancing national development interests with global climate commitments. Environmental diplomacy is utilized as an instrument to enhance Indonesia's bargaining position in obtaining green investment, transition funding, and technical support.